Value of permanent crops in the gross value added in agriculture - Grujić-Vučkovski Biljana Lj.; Vukićević Ksenija R.; Stevanović Dragana D. (Journal of Agricultural Sciences (Belgrade))
The aim of the research is to analyze the impact of the value of the production of permanent crops (fruit and viticulture sector) on the realized gross value added (GVA) in agriculture in Serbia and the EU from 2012 to 2022. The results were obtained by applying a multiple regression model where the dependent variable is the GVA in agriculture, and the independent variables represent the production values of the fruit and viticulture sector (in EUR mln). The coefficients of the model were tested using the t-test, and the model was verified using the F-test at a significance level of 0.05. The value of the standardized beta coefficient shows that the fruit-growing sector had a greater influence on the realized GVA of agriculture in Serbia and the EU (0.532 vs. 0.852), the t-values for Serbia belonged to the critical area in both sectors, while the t-values for the viticulture sector in the EU did not belong to the critical area. The F-test values show that the fitted model was significant at the 0.05 level for both observation areas. An analysis of the presence of multicollinearity in the independent variables was also conducted, and the results showed that there was a weak multicollinearity originating from the value of viticulture production.